2020
DOI: 10.3390/su12072826
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Evaluation of Financing Platform Operation of Buildings Energy Saving Transformation Using ANP-Fuzzy in China: An Empirical Study

Abstract: Building energy saving transformation is an inevitable requirement to achieve sustainable development, which can bring considerable economic, environmental, and social benefits. The key to healthy development of the market lies in the orderly operation of the financing platform. The effectiveness of the financing platform depends on scientific evaluation. Therefore, it is necessary to design a set of systematic and practical evaluation indicators for operational effectiveness of the buildings energy saving tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…e ANP model can measure all possible interrelationships among criteria while the analytic hierarchy process or rating law cannot [90]. In the case where the research object needs to consider and quantify the correlation among some criteria, ANP provides a more realistic method and better analysis for decisionmaking problems.…”
Section: Anp-entropy Weight Methodmentioning
confidence: 99%
“…e ANP model can measure all possible interrelationships among criteria while the analytic hierarchy process or rating law cannot [90]. In the case where the research object needs to consider and quantify the correlation among some criteria, ANP provides a more realistic method and better analysis for decisionmaking problems.…”
Section: Anp-entropy Weight Methodmentioning
confidence: 99%
“…Previous studies have confirmed the efficiency of the FANP for criteria weighting [61]. The FANP method is one of the most frequently used methods for computing the criteria's intrinsic weights [83][84][85][86][87]. To apply the FANP, we used the initial criteria ranking obtained in the pairwise comparison matrix based on expert opinions.…”
Section: Criteria Weighting and Sensitivity Analysismentioning
confidence: 99%
“…Therefore, the linear function was used to convert the classified raster layers to fuzzy standard layers, in which the pixel values ranged between zero and one. The FANP approach is a popular assessment method that combines the analytical network process method with the fuzzy level evaluation method [84,85]. Furthermore, the fuzzification allows us to quantitatively evaluate the qualitative criteria through fuzzy mathematics membership theory in complex decision-making [86].…”
Section: Criteria Weighting and Sensitivity Analysismentioning
confidence: 99%
“…Economidou et al [23] established a professional financing platform as an effective way to enhance the confidence of other participants. Guo et al [24] analyzed the effectiveness evaluation content of the operation of the building energysaving retrofitting financing platform from the two levels of the operating mechanism and the behavior of the operating subject. Existing scholars have conducted in-depth research on how to solve the financing problem of green retrofitting.…”
Section: Literature Reviewmentioning
confidence: 99%